Direct Observation of the Growth of Lithium Dendrites on Graphite Anodes by Operando EC‐AFM. Issue 2 (20th December 2017) - Shen, Cai; Hu, Guohong; Cheong, Ling‐Zhi; Huang, Shiqiang; Zhang, Ji‐Guang; Wang, Deyu
Abstract: Lithium dendrite growth is one of the most challenging problems affecting the safety performance of lithium‐ion batteries (LIBs). It causes low Coulombic efficiency as well as safety hazards for LIBs. Understanding the evolution process of Li‐dendrite growth at the nanoscale is critical for solving this problem. Herein, an in situ electrochemical atomic force microscopy (EC‐AFM) investigation of the initial Li deposition in ethylene carbonate (EC)‐based and fluoroethylene carbonate (FEC)‐based electrolytes on graphite anodes is reported. These results show that the solid electrolyte interphase (SEI) formed from the FEC‐based electrolyte can suppress Li‐dendrite growth. The FEC‐based electrolyte induces formation of LiF‐rich SEI films, which are harder and denser than those formed in an EC‐based electrolyte. Due to its better mechanical properties and larger resistance, the SEI layer formed from the FEC‐based electrolyte is sufficient to prevent reduction of Li + ions and deposition of Li + ions on the anode surface. These results demonstrate that EC‐AFM is a powerful in situ technique for the study of lithium‐dendrite growth. Abstract : Lithium dendrite growth is a challenging problem affecting the safety performance of lithium‐ion batteries. Due to the lack of reliable in situ techniques, a detailed mechanism of how dendrite growth occurs is still missing. An in situ electrochemical atomic force microscopy (EC‐AFM) investigation of the initial Li deposition in ethylene‐carbonate‐ and fluoroethylene‐carbonate‐based electrolytes on graphite anodes is reported.